Knowledge and Attitude towards HIV/AIDS among transsexuals in Kuantan, Pahang - D, Samsul; MR, Razman; M, Ramli; MA, Mohd Aznan; S, Maliya; MA, Muhamad Shaiful Lizam; MH, Muhammad Salman; H, Mohamad Faqihuddin (IIUM Medical Journal Malaysia, 2016)
Introduction: Lack of knowledge and negative attitude towards HIV/AIDS may be the risk factors for HIV infection among transsexuals. Research on knowledge and attitude towards HIV infection in transsexual communities is very limited at both local and international levels. This study aimed to assess the knowledge and attitude towards HIV infection among the male-to-female transsexual community in Kuantan, Pahang. Methods: A cross-sectional study was carried out from July to August 2014 among 33 male-to-female transsexuals in Kuantan, Pahang. Convenience sampling was used. Participants who gave consent answered a self-administered questionnaire. Data obtained was analyzed with descriptive statistics, χ 2 -test, and independent sample t test. Results: The majority of the subjects in this study were 29 years and below (48.5%), Muslims (93.9%), and had completed up to secondary education (60.6%). Most of them were sex workers (60.6%), and had relatively low income (no income to RM 3000, mean of RM1528). A total of 87.9% of the subjects demonstrated good knowledge and also positive attitude towards HIV/AIDS. Level of education was significantly associated with scores in knowledge (p=0.01). Conclusions: Despite the positive outcome from this study, misconceptions towards HIV/AIDS still exist among transsexuals. Education and interventions from multiple directions on HIV/AIDS are essential to deliver the correct information to this population, so as to emphasize prevention, early detection, and holistic medical care. Transsexuals also require attention from religious bodies and non-governmental organizations to help them in employment, financial, spiritual, and psycho-social issues.